INTEGRASI ARITMATIKA SOSIAL BERBASIS DUNIA KERJA DALAM PEMBELAJARAN MATEMATIKA - Dewanggita Aldora; Rachmawati (Universitas Teknokrat Indonesia, 2026)
This study aims to describe the integration of social arithmetic concepts based on the world of work in mathematics learning, analyze the implementation of learning, measure students' conceptual understanding, and examine students' responses and learning motivation. The study used a qualitative approach with a descriptive research type and case study design. The research subjects consisted of 24 seventh-grade female students of MTs An-Nur Al-Huda. Data collection was carried out through observation, conceptual understanding tests, student response questionnaires, interviews, and documentation. Data analysis used qualitative descriptive analysis techniques through the stages of data reduction, data presentation, and conclusion drawing. The results of the study showed that the implementation of learning reached an average of 85.25% with a very good category. The results of the conceptual understanding test showed that 41.7% of students were in the high category, 45.8% were in the medium category, and 12.5% ​​were in the low category. In addition, students' responses to learning obtained an average of 88.2% with a very good category. The interview results showed that students found it easier to understand the concepts of profit, loss, discounts, and percentages because the learning was linked to economic activities and the world of work that were close to their lives. Learning also increases student activity, motivation, and engagement throughout the learning process. Thus, the integration of workplace-based social arithmetic concepts can be effectively implemented and become a contextual, meaningful learning alternative that enhances students' conceptual understanding and motivation.